2020
DOI: 10.3390/molecules25235677
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activities and Therapeutic Potentials of Baicalein Extracted from Oroxylum indicum: A Systematic Review

Abstract: In Southeast Asia, traditional medicine has a longestablished history and plays an important role in the health care system. Various traditional medicinal plants have been used to treat diseases since ancient times and much of this traditional knowledge remains preserved today. Oroxylum indicum (beko plant) is one of the medicinal herb plants that is widely distributed throughout Asia. It is a versatile plant and almost every part of the plant is reported to possess a wide range of pharmacological activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Another compound present in Scutellaria baicalensis , but also in Oroxylum indicum , is baicalein [ 117 , 118 ]. Same as the abovementioned flavonoids, baicalein was found to be active against a variety of cancer cells and thereby acted via different pathways [ 119 ], however, also with limited oral bioavailability [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another compound present in Scutellaria baicalensis , but also in Oroxylum indicum , is baicalein [ 117 , 118 ]. Same as the abovementioned flavonoids, baicalein was found to be active against a variety of cancer cells and thereby acted via different pathways [ 119 ], however, also with limited oral bioavailability [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…The application of baicalein, as a main bioactive ingredient extracted from the root of medical herb Scutellaria baicalensis , has been studied in the treatment of a variety of cancers, such as breast cancer, NSCLC, nasopharyngeal carcinoma, hepatocellular carcinoma, and the underlying mechanisms mainly focus on inducing apoptosis and autophagy, cell cycle arrest, inhibiting proliferation and invasion of tumor cells ( Bie et al, 2017 ; Yan et al, 2018 ; Guo et al, 2019 ; Nik Salleh et al, 2020 ; Zhang et al, 2020 ). In addition to malignant cells, increasing evidence demonstrated the dominant role of the large proportions of immune cells within the TME in orchestrating tumor progression and resistance to anti-tumor drugs ( Cassetta and Pollard, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria baicalensis (also known as Chinese Huang Qin) is one of the most widely used herbs in TCM formula for treating various diseases, such as diarrhea, insomnia, and acute respiratory infection. Baicalein, one of the major bioactive compounds isolated from Scutellaria baicalensis, has been demonstrated multiple pharmacological effects, including anti-inflammatory, antiviral, anti-adipogenesis and cardiovascular protective effects ( Liu et al, 2016 ; Nik Salleh et al, 2020 ). Recent studies revealed that baicalein exerted anti-tumor activities in various solid tumors, such as non-small-cell lung cancer (NSCLC), and breast cancer ( Yan et al, 2018 ; Zhao et al, 2018 ; Nik Salleh et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteolin possesses an antibacterial effect in vivo, increasing membrane permeability [ 17 ], but does not directly perturb the model membranes in vitro [ 18 , 19 ]. Both baicalein and luteolin possess antitumor activity [ 20 , 21 ] and, as well as their derivatives, have been used in preclinical studies and in experimental oncology [ 22 , 23 , 24 , 25 , 26 , 27 ]. Epidemiological studies showed that foods rich in polyphenolic compounds (flavonoids, phenolic acids, lignans and stilbenes) included in the diet reduced the total risk of cancer by up to 50% [ 28 ].…”
Section: Introductionmentioning
confidence: 99%